Spatial distribution and diversity of bird community in an urban area of Southeast Brazil - Marco Antônio Manhães; Alan Loures-Ribeiro (Brazilian Archives of Biology and Technology, 2005)
Since the campus of the Federal University of Juiz de Fora, Minas Gerais State, Brazil, has different landscapes, it turns up to be a useful ecological model to evaluate the influence of habitat heterogeneity on bird communities. Our research goals were to know the local avifauna and compare its composition and bird diversity within the different landscapes. Species were identified in point counts without distance estimation, in four habitats: secondary woodlot, lake and surroundings, scrub/abandoned grazing areas and urban areas. One hundred and twenty-one species were identified, but no difference in diversity among the habitats was found. However, analyses indicated the existence of greater similarities among the sampling points belonging to the same kind of habitat. Results suggests that small and isolated forest fragments in urban areas fail to sustain a greater diversity than the adjacent areas, even though the environment's heterogeneous aspect favours local bird richness. O Campus da Universidade Federal de Juiz de Fora possui diferentes paisagens e pode representar um modelo ecológico útil para avaliar a influência da heterogeneidade de hábitats sobre a diversidade de aves. Os objetivos deste trabalho foram conhecer a avifauna local e comparar a composição e diversidade de aves nas distintas paisagens existentes. As espécies foram identificadas em pontos de contagem, em quatro hábitats: mata secundária, lago e arredores, capoeira/pastagem abandonada e urbanizada/jardinada. Foram identificadas 121 espécies, mas não houve diferença de diversidade entre os hábitats. Entretanto, as análises indicaram a existência de maiores similaridades entre os pontos amostrais pertencentes ao mesmo tipo de hábitat. Os resultados sugerem que pequenos fragmentos de mata fortemente isolados em áreas urbanas não sustentam uma diversidade maior do que as áreas adjacentes mas o aspecto heterogêneo do ambiente pode favorecer a riqueza de aves local.